Long-term clinical follow-up of patients suffering from moderate-to-severe COVID-19 infection: a monocentric prospective observational cohort study. (August 2021) - Darcis, Gilles; Bouquegneau, Antoine; Maes, Nathalie; Thys, Marie; Henket, Monique; Labye, Florence; Rousseau, Anne-Françoise; Canivet, Perrine; Desir, Colin; Calmes, Doriane; Schils, Raphael; De Worm, Sophie; et al.
Highlights: Post-coronavirus disease 2019 (COVID-19) conditions are common. The prevalence of tiredness up to 6 months after COVID-19 is high. The prevalence of shortness of breath up to 6 months after COVID-19 is high. Pulmonary function tests improved during follow-up. Chest computed tomography scan at 3 months after discharge showed that most images were improved. ABSTRACT: Objectives: Various symptoms and considerable organ dysfunction persist following infection with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Uncertainty remains about the potential mid- and long-term health sequelae. This prospective study of patients hospitalized with coronavirus disease 2019 (COVID-19) in Liège University Hospital, Belgium aimed to determine the persistent consequences of COVID-19. Methods: Patients admitted to the University Hospital of Liège with moderate-to-severe confirmed COVID-19, discharged between 2 March and 1 October 2020, were recruited prospectively. Follow-up at 3 and 6 months after hospital discharge included demographic and clinical data, biological data, pulmonary function tests (PFTs) and high-resolution computed tomography (CT) scans of the chest. Results: In total, 199 individuals were included in the analysis. Most patients received oxygen supplementation (80.4%). Six months after discharge, 47% and 32% of patients still had exertional dyspnoea and fatigue. PFTs at 3-month follow-up revealed a reduced diffusion capacity of carbon monoxide (mean 71.6 ± 18.6%), and this increased significantly at 6-month follow-up ( P <0.0001). Chest CT scans showed a high prevalence (68.9% of the cohort) of persistent abnormalities, mainly ground glass opacities. Duration of hospitalization, intensive care unit admission and mechanical ventilation were not associated with the persistence of symptoms 3 months after discharge. Conclusion: The prevalence of persistent symptoms following hospitalization with COVID-19 is high and stable for up to 6 months after discharge. However, biological, functional and iconographic abnormalities improved significantly over time.